Development and Mechanistic Investigation of Indium(III)-Catalysed Hydrosilane Reduction of Imines - Petersen, Nadia Nasser (Apollo - University of Cambridge Repository, 2019)
Asymmetric catalysis continues to be of utmost importance inter alia for the development of enantiomerically pure drugs. The application of computational methods in understanding how enantioselectivity is induced in specific reactions is a powerful time-saving tool for organic chemists. By investigating the reaction pathway, specifically the enantiodetermining transition state, factors that result in an increased energy difference between the two enantiomeric transition states can be identified and thus employed for increasing the enantiomeric excess. Little is known regarding the achievement of enantioselectivity in indium(III)-catalysed reactions. Hence, the project described in this dissertation has started from scratch by generating the experimental data from which to build computational models. This dissertation starts with an introduction to the field of asymmetric catalysis, the advantages of indium as a catalyst and recent progress within indium-catalysed reactions. Following is a discussion of an extensive methodology project where complexes of In(III) and various functionalised BINOL ligands or BINOL derivatives have been investigated as catalysts for the hydrosilane reduction of imines. The functionalised BINOL ligands employed include a range of C1-symmetric BINOL ligands, which were synthesised as part of a project on optimising BINOL phosphoric acid ligands described in Chapter 2. Significant progress has been made towards the development of a catalyst complex capable of achieving an enantioselective In(III)-catalysed reduction. The developed methodology presented in this thesis represents a novel method for achieving enantioselectivity in prochiral substrates by the use of chiral ligands co-ordinating to an indium metal-centre. Enantiomeric excess was obtained only in polar, protic solvent systems, where up to 73% e.e. was achieved. The experimental work has been combined with computational investigations of potential complexes and mechanistic pathway calculations. The most plausible pathway, established from the computational investigations presented in this thesis, proceeds via the formation of an In(III)-hydride species. This hydride is then transferred to the imine in the manner observed in ruthenium-catalysed reactions. Preliminary results for an alternative active In(III)-In(III) dimeric complex is discussed. Extensive experimental mechanistic investigations are presented along with a substrate scope of the reaction. Finally, future perspectives are given on how the knowledge obtained regarding the enantiodetermining mode in the investigated hydrosilane reduction might be employed to achieve enantioselectivity in other In(III)-catalysed reactions.
Keywords: Indium; catalysis; enantioselectivity; DFT; hydrosilane reduction